Inequalities between Māori and non-Māori men with prostate cancer in Aotearoa New Zealand. - Egan R; Kidd J; Lawrenson R; Cassim S; Black S; Blundell R; Bateman J; Broughton J (Pasifika Medical Association Group (PMAG) previously New Zealand Medical Association (NZMA), 2020)
Māori experience poorer health statistics in terms of cancer incidence and mortality compared to non-Māori. For prostate cancer, Māori men are less likely than non-Māori men to be diagnosed with prostate cancer, but those that are diagnosed are much more likely to die of the disease than non-Māori men resulting in an excess mortality rate in Māori men compared with non-Māori. A review of the literature included a review of the epidemiology of prostate cancer; of screening; of access to healthcare and of treatment modalities. Our conclusion was that there are a number of reasons for the disparity in outcomes for Māori including differences in staging and characteristics at diagnosis; differences in screening and treatment offered to Māori men; and general barriers to healthcare that exist for Māori men in New Zealand. We conclude that there is a need for more culturally appropriate care to be available to Māori men.
Keywords: Adult; Aged; Healthcare Disparities; Humans; Male; Middle Aged; Native Hawaiian or Other Pacific Islander; New Zealand; Prostatic Neoplasms; Risk Factors; Socioeconomic Factors; White People